I've got sand in all the wrong places - Scottoline, Lisa; Serritella, Francesca Scottoline (New York St. Martin's Press, 2016)
"Lisa and Francesca are back with another collection of warm and witty stories that will strike a chord with every woman. This six book series is among the best reviewed humor books published today and has been compared to the late greats, Erma Bombeck and Nora Ephron. Delia Ephron said of the fifth book in the series, Have a Nice Guilt Trip, "Lisa and Francesca, mother and daughter, bring you the laughter of their lives once again and better than ever. You will identify with these tales of guilt and fall in love with them and fierce (grand) Mother Mary." This seventh volume will not disappoint as it hits the humorous and poignant note that fans have come to expect from the beloved mother-daughter duo"--
1
Keywords: Scottoline, Lisa; Serritella, Francesca Scottoline; FAMILY & RELATIONSHIPS / Parenting / Parent & Adult Child; HUMOR / Form / Essays; Mothers and daughters -- Humor; Women -- Humor